Social and political Implications of Economic Liberalization in South Asia : Politics of Reform in India: Kerala Model Under Pressure - K Ravi Raman
The southernmost state in India, Kerala, has been a subject of academic analysis down the years. This owes largely to the remarkable levels of social achievement - universal literacy, low mortality, low child mortality, high life expectancy at birth, social security net works - attained by the state which is even comparable to the West. But the neo-liberal reforms in the crucial sectors such as Public Resources, Power, Urban Development, Environmental Improvement and Poverty Reduction with Asian Development Bank policy loan has brought into focus mixed responses.